La educación moral en la infancia y adolescencia - Ortega Ruiz, Pedro; Mínguez Vallejos, Ramón (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this paper, the necessity for a moral education in childhood and adolescence is emphasized, and an exposition of its basic guidelines is presented: the learning of social skills/competences throughout cooperative learning and self-government in the classroom; the use of moral dilemmas and the clarification of values; the establishment of a respectful and dialoguing atmosphere in the family. All these guidelines are presented as adequate resources for a moral education in childhood and adolescence.